Finding of the optimal preparation and timing of endometrium in frozen-thawed embryo transfer: a literature review of clinical evidence - Hsueh, Ya-Wen; Huang, Chien-Chu; Hung, Shuo-Wen; Chang, Chia-Wei; Hsu, Hsi-Chen; Yang, Tung-Chuan; Lin, Wu-Chou; Su, Shan-Yu; Chang, Hsun-Ming (Frontiers in Endocrinology, 2023)
Frozen-thawed embryo transfer (FET) has been a viable alternative to fresh embryo transfer in recent years because of the improvement in vitrification methods. Laboratory-based studies indicate that complex molecular and morphological changes in endometrium during the window of implantation after exogenous hormones with controlled ovarian stimulation may alter the interaction between the embryo and endometrium, leading to a decreased implantation potential. Based on the results obtained from randomized controlled studies, increased pregnancy rates and better perinatal outcomes have been reported following FET. Compared to fresh embryo transfer, fewer preterm deliveries, and reduced incidence of ovarian hyperstimulation syndrome were found after FETs, yet there is a trend of increased pregnancy-related hypertensive diseases in women receiving FET. Despite the increased application of FET, the search for the most optimal priming protocol for the endometrium is still undergoing. Three available FET protocols have been proposed to prepare the endometrium: i) natural cycle (true natural cycle and modified natural cycle) ii) artificial cycle (AC) or hormone replacement treatment cycle iii) mild ovarian stimulation (mild-OS) cycle. Emerging evidence suggests that the optimal timing for FET using warmed blastocyst transfer is the LH surge+6 day, hCG administration+7 day, and the progesterone administration+6 day in the true natural cycle, modified natural cycle, and AC protocol, respectively. Although still controversial, better clinical pregnancy rates and live birth rates have been reported using the natural cycle (true natural cycle/modified natural cycle) compared with the AC protocol. Additionally, a higher early pregnancy loss rate and an increased incidence of gestational hypertension have been found in FETs using the AC protocol because of the lack of a corpus luteum. Although the common clinical practice is to employ luteal phase support (LPS) in natural cycles and mild-OS cycles for FET, the requirement for LPS in these protocols remains equivocal. Recent findings obtained from RCTs do not support the routine application of endometrial receptivity testing to optimize the timing of FET. More RCTs with rigorous methodology are needed to compare different protocols to prime the endometrium for FET, focusing not only on live birth rate, but also on maternal, obstetrical, and neonatal outcomes.